BRAIN MACHINE INTERFACES: a ray of hope - & Alok Kumar Verma, Vineeta Yadav Rizwana Zamal (International Journal of Scientific Research and Management (IJSRM), 2014)
Neuroscientists have long relished the possibility of using brain signals to control artificial devices. Already, in literature there are several devices such as brain-actuated technology, neuroprosthes or neurorobots collectively refer as hybrid brain machine interfaces (HBMI) [1]. The word hybrid means a continuous interaction between living brain and artificial electronic devices. HBMI uses mainly in two types of applications